Inkonsistensi Mahkamah Agung Dalam Menerapkan Perlindungan Hukum Terhadap Merek Terkenal Dalam Sengketa Merek - Antonius Ivananda Dias Wijaya; Diana Tantri Cahyaningsih (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
This legal writing aims to examine and analyze the inconsistency of the Supreme Court in providing protection for well-known brands in Indonesia. This research is normative legal research that is prescriptive in nature. The approaches used in this research are the statutory approach, case approach, comparative approach and conceptual approach. This research uses primary legal materials, statutory regulations and Supreme Court decisions relating to well-known trademark disputes as well as secondary legal materials in the form of research results discussing trademark disputes. The results of this research are that the Supreme Court decisions studied in this research conclude that there is inconsistency in the Supreme Court in providing protection for well-known brands. The Supreme Court has not been able to provide an appropriate protection mechanism in dealing with the legal vacuum regarding the definition of a Famous Mark. This has implications for various interpretations in considering the popularity of a brand. The considerations given by the Supreme Court have not shown justice and continuity with the ratification of international agreements regarding the legal protection of well-known marks. Where judges should be able to refer to jurisprudence in resolving famous brand disputes, this research concludes that there are inconsistencies in this matter so that legal certainty has not been created regarding the protection of famous brands.